Paphiopedium fairieanum (Lindl) Pfitz.-Habitat, Descriptive and Cultural Notes - Rao, A. S.; Hajra, P. K. (Indian Forester, 1977)
Paphiopedilum fairieannum (Lindl.) pritz., an elegant lady-slipper orchid, from Kameng district, Arunachal Pradesh, has been described with note on its natural habitat and culture. Suggestions on its conservation have also been given.